2023
DOI: 10.15252/emmm.202217313
|View full text |Cite|
|
Sign up to set email alerts
|

ATR inhibition augments the efficacy of lurbinectedin in small‐cell lung cancer

Abstract: Small‐cell lung cancer (SCLC) is the most lethal type of lung cancer. Specifically, MYC‐driven non‐neuroendocrine SCLC is particularly resistant to standard therapies. Lurbinectedin was recently approved for the treatment of relapsed SCLC, but combinatorial approaches are needed to increase the depth and duration of responses to lurbinectedin. Using high‐throughput screens, we found inhibitors of ataxia telangiectasia mutated and rad3 related (ATR) as the most effective agents for augmenting lurbinectedin effi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…LUR has been evaluated in combination with ICIs (anti-PD-L1 and anti-CTLA-4 [ 152 ]) and in combination with irinotecan [ 153 , 154 ], ATR [ 122 , 155 ] alone or combined with ATM [ 156 ] and PARP [ 157 ] inhibitors, anti-VEGF [ 158 ] combined with cisplatin [ 83 , 159 , 160 ], paclitaxel [ 158 ], gemcitabine [ 161 ], capecitabine [ 162 ], doxorubicin [ 41 , 163 , 164 ], and immunomodulatory biomolecules such as antibody-drug complexes commonly referred to as ADCs (4C9-DM1 that targets c-Kit [ 165 ]).…”
Section: Combination Therapies Involving Trabectedin and Lurbinectedinmentioning
confidence: 99%
See 2 more Smart Citations
“…LUR has been evaluated in combination with ICIs (anti-PD-L1 and anti-CTLA-4 [ 152 ]) and in combination with irinotecan [ 153 , 154 ], ATR [ 122 , 155 ] alone or combined with ATM [ 156 ] and PARP [ 157 ] inhibitors, anti-VEGF [ 158 ] combined with cisplatin [ 83 , 159 , 160 ], paclitaxel [ 158 ], gemcitabine [ 161 ], capecitabine [ 162 ], doxorubicin [ 41 , 163 , 164 ], and immunomodulatory biomolecules such as antibody-drug complexes commonly referred to as ADCs (4C9-DM1 that targets c-Kit [ 165 ]).…”
Section: Combination Therapies Involving Trabectedin and Lurbinectedinmentioning
confidence: 99%
“…For LUR in combination with ICIs: anti-PD-L1 and anti-CTLA-4 showed strong anti-neoplastic effects in osteosarcoma and fibrosarcoma cell lines, and breast cancer and fibrosarcoma murine models [ 152 ]. LUR + berzosertib (ATR inhibitor) showed synergy in SCLC in vivo, organoid, and in vitro models [ 155 ]. LUR + cisplatin showed promising activity in malignant pleural mesothelioma [ 160 ] but it was not feasible in advanced solid tumours due to toxicity issues [ 83 ].…”
Section: Combination Therapies Involving Trabectedin and Lurbinectedinmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was preclinically observed that the RNA Pol-II inhibitor lurbinectedin, which induces DNA damage, exhibited strong synergy with the ATR inhibitor berzosertib in SCLC cell lines. Synergy was reduced with high p21 expression, as p21 causes G1 arrest [ 66 ]. It could be possible that SCLC cells with p53 aberrations, and thus reduced levels of the protein p21, would respond better to the combination of berzosertib and lurbinectedin.…”
Section: Targeted Therapies In P53 and Rb Deficient Sclc Cellsmentioning
confidence: 99%
“…In combination with topotecan, it has a cytotoxic effect and activates the STING (STimulator of INterferon Genes) pathway, implying that ATR-TOP1 inhibition may improve response to immune checkpoint therapy in STING-low SCLC tumors [ 80 ]. In addition, synergy of M6620 with lurbinectedin has been demonstrated in multiple SCLC cell lines, organoids, and in vivo models [ 81 ], and their combined effectiveness is currently being assessed in a clinical trial (NCT04802174). Finally, other M6620 combinations are under investigation in SCLC, such as a combination with the Trop2 inhibitor molecule sacituzumab-govitecan (NCT04826341), a transmembrane glycoprotein that has emerged as a promising molecular target for lung cancer treatment [ 82 ].…”
Section: Actionable Drivers In Sclcmentioning
confidence: 99%